Dynamic Interpretation of International Investment Treaties - Tao, Zihan (International Journal of Global Economics and Management, 2025)
The legal regime of international investment treaties (IITs) is an important part of international economic law, designed to provide legal protection for cross-border investment through bilateral investment agreements (BITs) and multilateral investment agreements (MIAs). However, with the changes in the global economic landscape, the current system faces many challenges in terms of investor-state dispute settlement (ISDS) mechanism and other aspects. By sorting out the historical evolution of international investment treaties, analysing the practical problems of the international investment treaty mechanism and exploring the path of institutional reform, we hope to provide reference for the construction of a fairer and more efficient international investment legal system.